Diaspora et communautés arméniennes : - Dzovinar Kévonian (Diasporas: Circulations, Migrations, Histoire)
This article offers a general overview of Armenian-language historiography on the Armenian diaspora and communities, and issues of production, dissemination and reception. It includes interviews with Antranik Dakessian (Armenian Diaspora Research Center, Beirut), Mikael Nichanian (BnF, Paris) and Adrineh Zinali (Bulac, Paris).